The Effects of Temperature on Dynamics of Psychiatric Outpatients - Shao, Ying; Xu, Jiahui; Qiao, Ying; Shao, Yang; Fei, Jian-Ming (Frontiers in Psychiatry, 2020)
Background: Climate changes affect mental states and alter the risk for psychiatric diseases. Seasonal changes in temperature lead to dynamics in occurrence of psychiatric conditions, and poses challenge on administration of clinical psychiatry services. Methods: The present study aims to retrospectively analyze outpatients data with weather reports in past five years (Jan 2014 - Mar 2019) in Shanghai Mental Health Center, one of the largest psychiatric hospitals in the world , in order to provide policy insights on administration of psychiatric clinics. Results: The results showed steady increases in overall patients over the past five years, with several peaks within the year. Temperature change and weather information reliably predicts the increased psychiatric patients. Conclusions: We conclude that mental health hospital should prepare for patient dynamics based on weather forecasts.